Environmental nanotechnology: applications and impacts of nanomaterials - Wiesner, Mark R. (New York, 2007)
"Explore the properties of today's widely used nanomaterials - and assess their potentially harmful effects on the environment. "Environmental Nanotechnology" is the first book to assist you in both understanding the properties of new nanomaterial-centered technology and assessing the potentially harmful effects these materials may have on the environment. Written by a team of 29 leading experts from around the world, this comprehensive book presents: cutting-edge coverage of the fabrication, characterization, and measurement of nanomaterials; emerging markets for nanomaterials; nanotechnologies in the energy industry; nanotechnologies for environmental quality; nanotechnology transport and fate in the environment; toxicological impacts of nanomaterials; and much more.Filled with detailed illustrations, "Environmental Nanotechnology" features: state-of-the-art techniques for the characterization and measurement of nanomaterials; the latest findings on the transport and fate of nanomaterials in the environment; nanotechnologies for energy production, storage, and distribution; in-depth analyses of the ecotoxicological impacts of nanomaterials; new methods for developing nanomaterials with less environmental risk. Inside this landmark Environmental Engineering guide you'll find: Nanomaterials - new challenges and opportunities; fabrication of Nanomaterials; characterization and measurement of Nanomaterials; emerging markets for Nanomaterials; Nanomaterial-Enabled technologies for Energy Production, Storage, and Distribution; Nanomaterial-Enabled technologies for Environmental Quality; Nanomaterial transport and fate in the environment; ecotoxicological impacts of Nanomaterials; and toxicological impacts of Nanomaterials."